Therapy Talk - Fitzgerald, P. author. aut Link
XII, 195 p.
Keywords: Therapy Talk aims to help those who apply 'the talking cure' become better at their jobs by enabling them to understand how their verbal responses may channel the conversation partner into a particular direction, promoting conversation analysis as a useful tool to study and enhance the therapeutic alliance between client and practitioner.